(untitled) (CSIAM Transactions on Life Sciences, 2025)
This paper overviews the recent advances how spatial-temporal heterogeneity affects the spread of epidemic diseases from the perspective of basic reproduction number. First part focuses upon the theoretical studies and applications of seasonal effects on infectious invasion. Then the investigations are introduced to demonstrate the role of spatial structure and spatial contact patterns in the prevention of disease outbreaks. Suggestions are presented for potential future researches.